تأثير تنمية قوة وثبات عضلات المركز علي مستوي أداء مهارة الكودي للاعبي جمباز الترامبولين - عبد ربه، سعيد محمد غنيمي محمد (جامعة الأسكندرية - كلية التربية الرياضية للبنين بأبوقير, 2023)
يهدف البحث إلى التعرف على تأثير تنمية قوة وثبات عضلات المركز على تحسين مستوي أداء مهارة الكودي للاعبي جمباز الترامبولين، تم استخدام المنهج التجريبي باستخدام التصميم التجريبي ذو القياس القبلي البعدي للمجموعة الواحدة، تكونت عينة البحث من (۱۱) لاعبا من لاعبي الدرجة الثانية وتحت ١٤ سنه، لجمباز الترامبولين بنادي العاملين بكليه التربية الرياضية للبنين بالإسكندرية ونادي الاتحاد السوداني العام بالقاهرة موسم ۲۰۲۲ - ۲۰۲۳، بعد تطبيق البرنامج تم التوصل إلى: - يؤثر برنامج قوة وثبات عضلات المركز والذي خضعت له عينه البحث تأثيرا إيجابيا في جميع القياسات البدنية قيد البحث. - يؤثر برنامج قوة وثبات عضلات المركز والذي خضعت له عينه البحث تأثيرا إيجابيا مستوي أداء مهارة الكودي لعينه البحث. ومن خلال هذه النتائج يوصى الباحث بالآتي:- - الاسترشاد بالأسس العلمية التي استخدمت في تصميم البرنامج التدريبي المقترح والتي تشتمل على تدريبات قوة وثبات عضلات المركز، لمهارات جمباز الترامبولين. - توجيه النتائج المستخلصة إلى العاملين بمجال الجمباز للاستفادة منها في برامج التدريب المختلفة. - إجراء المزيد من البحوث الدراسة مدى جدوى تنميه قوة وثبات عضلات المركز، على الأداء العملي المهارات الجمباز. - تدعيم الأداء العملي لجميع مهارات الجمباز بتدريبات قوة وثبات عضلات المركز، لما له من أثر في تحسين أداء المهارات. The research aims to identify the effect of developing the strength and stability of the center muscles on improving the level of performance of the cody skill for trampoline gymnasts, the experimental approach was using the experimental design with pre-post-measurement for one group, the research sample consisted of (11) second-class (junior) players and under 14 years old, for trampoline gymnastics at the Staff Club of the Faculty of Physical Education for Boys in Alexandria and the Sudanese General Union Club in Cairo, season 2022-2023, after applying the program, it was reached: - The program of strength and stability of the muscles of the center, which was subjected to the same research, has a positive effect on all physical measurements under study. - The program of strength and stability of the muscles of the center, which the research sample was subjected, has a positive effect on the performance level of the cody skill for the research sampl Through these results, the researcher recommends the following: Be guided by the scientific foundations that were used in designing the proposed training program, which includes strength and stability exercises for the center muscles, for trampoline gymnastics skills. Directing the findings to gymnastics workers to benefit from them in various training programs. Conducting more research to study the feasibility of developing the strength and stability of the core muscles, on the practical performance of gymnastics skills Strengthening the practical performance of all gymnastics skills with strength and stability exercises for the center muscles, because of its impact on improving the performance of the skills.
Keywords: رياضة الجمباز -- البرامج التدريبية -- الأداء المهاري -- الدورات الأولمبية